Impact of China’s diagnosis-intervention packet payment reform on pediatric pneumonia hospitalization costs: an interrupted time series analysis - Liang Zhao; Kun Zeng; Feijia Chen; Wei Li; Jun Zhao (Cost Effectiveness and Resource Allocation)
Abstract Background Pediatric pneumonia remains a major cause of morbidity and mortality, imposing substantial financial burdens on healthcare systems and families. This study evaluates the impact of China’s diagnosis-intervention packet (DIP) payment reform on hospitalization costs and care quality for pediatric pneumonia. Methods We retrospectively analyzed hospitalization cost data from a pilot hospital for DIP reform, between January 2019 and December 2023. Cases were categorized into re-reform and post-reform phases based on DIP implementation. Interrupted time series regressions assessed immediate and long-term cost trends and clinical outcomes. Results A total of 13,133 pediatric pneumonia hospitalizations were included (4,053 pre-reform; 9,080 post-reform). Median hospitalization costs decreased from 4,150.7 RMB to 3,853.3 RMB, with the most notable reductions in medication costs (261.1 RMB) and comprehensive service fees (103.9 RMB). Interrupted time series analysis showed significant immediate reductions in comprehensive service costs (23.2%, P < 0.001) and medication costs (15.8%, P = 0.031), followed by sustained monthly declines in all types of hospitalization costs. Concurrently, clinical outcomes improved: cure rates increased significantly from 87.0 to 90.6% (P < 0.001) without increased ICU transfers (3.5% vs. 4.6%, P = 0.478). Conclusion The implementation of DIP payment reform was associated with significant reductions in hospitalization costs for pediatric pneumonia while maintaining key quality indicators such as cure rates and ICU transfer frequencies. The observed cost reductions were primarily driven by lower medication expenses and reduced use of unnecessary diagnostic services, reflecting a shift towards value-based care. These findings underscore the potential of DIP reform to enhance hospital efficiency and financial sustainability without compromising patient care.